Espacios comunicativos para la convivencia y la participación. Pensamiento y práctica desde la IAP (2013)
The article describes an academic experience from Participant Action Research in the community of San Pedro de Tibabuyes (Suba, Bogotá-Colombia), in which the creation of a community newspaper as an alternative to social participation and integration was accompanied. A brief reflection on the notion of coexistence, participation and social ties generated and their limits is made.